Fabrication and photocatalytic property of magnetic NiFe2O4/Cu2O composites. (4th September 2017) - He, Zuming; Xia, Yongmei; Tang, Bin; Su, Jiangbin
Abstract: Magnetically separable NiFe2 O4 /Cu2 O composites were successfully synthesized by a two-step method. The samples were characterized by XRD, XPS, SEM and VSM as well as their PL spectra and UV–vis adsorption spectra. The results showed that the NiFe2 O4 /Cu2 O composites were composed of cubic-structured Cu2 O and spinel-structured NiFe2 O4, were able to absorb a large amount of visible light, exhibited excellent photocatalytic activity under simulated solar light irradiation and could be easily separated by an external magnetic field. The NiFe2 O4 /Cu2 O composites exhibited higher photocatalytic performance than that of a single semiconductor. It was found that the prominently enhanced photocatalytic performance of NiFe2 O4 /Cu2 O composites was ascribed to the effective separation of photo-generated electron–hole pairs and the effective generation of the hydroxyl radical OH.